Analisis Pengaruh Pengaturan Sudut Penyalaan Thyristor Pada Tegangan Eksitasi Terhadap Keluaran Daya Reaktif Generator di PT.PJB PLTU Gresik Unit 3 - Rachmat Sutjipto; Ika Noer Syamsiana; Widya Pratiwi Suryaningsih (Elposys: Jurnal Sistem Kelistrikan, 2021)
In this study, the excitation system used is a static excitation system that uses a transformer and several thyristors connected in a bridge configuration. The excitation system is then implemented on a generator with a capacity of 200 MVA / 15 kV using the MATLAB Simulink R2017b simulation. By using the above circuit, the thyristor ignition angle setting can be adjusted so that it can adjust the excitation voltage and obtain the appropriate excitation current to maintain the stability of the generator output voltage. The simulation was carried out with variations in generator load and using 2 different types of excitation settings. The first setting is to set the thyristor ignition angle to 30° with t=10 ms, at this setting the generator can maintain a stable V out value with a voltage regulation limit of ±5% and the reactive power that can be generated by the generator is +50MVAr and - 40 MVAr. When given a constant excitation at an angle of 35° with t=1 ms, the value of Vout exceeds the expected regulatory limit and the resulting reactive power limit is between +60 MVAr and -100 MVAR where the reactive power does not match the load requirements. This can have an impact on the interconnection system, namely when the reactive power of the generator is greater than the load requirement, the generator with a smaller reactive power will absorb reactive power in the interconnection system and can disrupt the stability of the interconnection network.